2011
DOI: 10.1097/ta.0b013e31821cb7e5
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Potentiates the Lethal Effect of Intestinal Ischemia-Reperfusion Injury: The Role of In Vivo Virulence Activation

Abstract: Introduction Experimental models of intestinal ischemia reperfusion (IR) injury are invariably performed in mice harboring their normal commensal flora, even though multiple intestinal IR events occur in humans during prolonged intensive care confinement when they are colonized by a highly pathogenic hospital flora. The aims of this study were to determine if the presence of the human pathogen P. aeruginosa in the distal intestine potentiates the lethality of mice exposed to intestinal IR and to determine what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Yet our work and the work of others have demonstrated that bacteria sense more than just a quorum [1621,37]. For example we have shown that the QS system can also sense and be activated by host compensatory molecules such as immune elements, end- products of hypoxia, and both endogenous and exogenous opioids [18,20]. Accidental pathogens, i.e.…”
Section: Commensal Microbes Stimulate Immunity and Suppress Inflammatmentioning
confidence: 64%
“…Yet our work and the work of others have demonstrated that bacteria sense more than just a quorum [1621,37]. For example we have shown that the QS system can also sense and be activated by host compensatory molecules such as immune elements, end- products of hypoxia, and both endogenous and exogenous opioids [18,20]. Accidental pathogens, i.e.…”
Section: Commensal Microbes Stimulate Immunity and Suppress Inflammatmentioning
confidence: 64%
“…Furthermore when sepsis syndrome and multiple organ failure develop post arrest, there is no evidence that they are causally linked to intestinal barrier failure (39). Although experimentally, elimination of the microbiota during intestinal ischemia reperfusion attenuates the permeability defect (40) and the presence of pathobiota exacerbate it (41), the extent to which the defined permeability defect is causative to the subsequent immunopathology and organ failure observed remains unknown.…”
Section: Intestinal Permeability Bacterial Translocation Intestinalmentioning
confidence: 99%
“…Pseudomonas aeruginosa MPAO1(10) and luminescent strain XEN41 (11) were used in the experiments. Strain XEN41 (Calpier, Inc) is a constitutively luminescent derivative of PAO1.…”
Section: Methodsmentioning
confidence: 99%